2022
DOI: 10.3390/su14063158
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Earth Blocks Using Sediments and Alkali-Activated Byproducts

Abstract: Sediment dredging is necessary and vital to preserve maritime activities and prevent floods. The management of these sediments represent an environmental challenge for many countries all over the world. This study focuses on evaluating the feasibility of using dredged sediments for the manufacturing of compressed earth blocks (CEB). The alternative construction material has the potential of reducing the need for dredged sediment onshore storage or ocean dumping. Several experimental tests have been conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Similar results were reported by [38,42,54,57]. Reference [29] used fly ash with ground blasted furnace slag to stabilize soil blocks and found that the 28-day compressive strength was significantly greater than that of the preceding studies. The CSEB displayed a compressive strength of 16.53 MPa.…”
Section: Compressive Strengthsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were reported by [38,42,54,57]. Reference [29] used fly ash with ground blasted furnace slag to stabilize soil blocks and found that the 28-day compressive strength was significantly greater than that of the preceding studies. The CSEB displayed a compressive strength of 16.53 MPa.…”
Section: Compressive Strengthsupporting
confidence: 74%
“…The CSEB displayed a compressive strength of 16.53 MPa. This is linked to the formation of hydrated calcium alumina silicate coexisting with geopolymer gels to form a vast, three-dimensional array of aluminosilicate [29].…”
Section: Compressive Strengthmentioning
confidence: 99%